How to think like an officer lessons in learning and leadership for soldiers and other citizens - Bonadonna, Reed (Stackpole Books, 2020)
"Drawing from military history, military arts, literature, science, and more, Reed Bonadonna shows how military officers develop their critical-thinking and problem-solving skills, how they can improve these skills, and how average civilians and citizens can learn from the example of military officers and their program of education"